2016
DOI: 10.18805/lr.v0i0.7842
|View full text |Cite
|
Sign up to set email alerts
|

Soybean cultivation by farmers of Maharashtra: Identification and analysis of the problems

Abstract: In Maharashtra, soybean is cultivated on an area of 3.8 M ha with production of 3.07 m ton with second rank in India. However, low productivity of the crop remains a major problem of soybean cultivation, necessitating the need to ascertain the problems faced by soybean growers. Therefore, a study was conducted in the 20 villages of five districts of western Maharashtra. A survey method using personal interview of 100 farmers and focused group discussion with villagers, were used for data collection during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…This may be due to communication gap with markets. Similar findings were observed by Miah et al [21], Mandal et al [23], Jaybhay et al [16].…”
Section: Marketing Problemsupporting
confidence: 90%
See 2 more Smart Citations
“…This may be due to communication gap with markets. Similar findings were observed by Miah et al [21], Mandal et al [23], Jaybhay et al [16].…”
Section: Marketing Problemsupporting
confidence: 90%
“…This might be during the peak period of cultivation labor scarcity prevails due to other agricultural cultivation. Jaybhay et al [16] found similar result in his research.…”
Section: Labor Problemsupporting
confidence: 76%
See 1 more Smart Citation
“…The generally poor crop management at Masemola was evidenced by the low biomass observed at flowering (Fig 2). Challenges observed at Masemola are similar to those reported for common bean farmers of Maharashtra in India (Jaybhay et al, 2018). However, the grain yield observed in this study particularly at Dalmada and Mokopane were within range of yields observed in the country.…”
Section: Above Ground Dry Biomass and Grain Yieldsupporting
confidence: 86%
“…Soybean [Glycine max (L.) Merrill] is one of the most important oilseed crops in India (Jaybhay et al 2018). The crop is called "Golden bean" or "Miracle crop" of the 21 st century because of its multiple uses (Jadhav 2014).…”
Section: Introductionmentioning
confidence: 99%